What Drives Perceived Value and Loyalty in Live Broadcasting - Kuan-Yin LEE; Prasana Kumar SAMANTA; Jing-Ya HUANG (Communications of International Proceedings, 2022)
The purpose of the present study is to analyze consumers’ loyalty to the brand and the broadcast owner in live broadcast e-commerce and to determine whether the brand in live broadcast e-commerce has enough influence to analyze whether live broadcast sales bring long-term value or result in the dilemma of short-term promotion. The present research is helpful to find the factors that affect the long-term interests and loyalty of the brand and provide  reference and contribution to the future development of live marketing in the industry.
Keywords: Live broadcast sales; Brand equity; Broadcaster loyalty; Brand loyalty